Board Games in the Classroom (Journal of Parents and Teachers, 2025)
Board games offer real potential as a resource to facilitate learning. Therefore, my undergraduate thesis proposes an annual curriculum for the English subject based on games. The objective is to incorporate active methodologies in the classroom that foster interest, participation, and knowledge acquisition. The aim is to deliberately create a safe and engaging environment for students that lays the foundation for meaningful learning.
Keywords: board games; educational planning; interdisciplinarity; language acquisition; active learning methodology